KEANEKARAGAMAN KUPU-KUPU DI TAMAN NASIONAL BANTIMURUNG BULUSARAUNG - Abdul Haris Mustari; Yasser Pramana; Resi Nurlinda (Media Konservasi, 2013)
Diversity of butterflies are supported by ecosystem of region, such as: forests, rivers, open land and diversity of plants. High biodiversity and a variety of unique and endemic species in Bantimurung Bulusaraung National Park can make this area become important for intensively managed. Inventory of butterflies in Bantimurung Bulusaraung National Park held in two locations, on 24th February until 1st March in 2011 at Panaikang district and 8th until 12 March in 2011 at Kampoang district. The method that used is time-search. Total number of butterflies that observed is 80 species with index of diversity value is high. This is because the Bantimurung Bulusaraung National Park has a lot of vegetation feed for butterflies and lots of water. Besides nectar from flowers, butterflies also need the minerals from sides of the river especially in the coral of river. Keywords: Biodiversity, butterfly, Bantimurung Bulusaraung National Park.